Qatar Katrina Fund : 10 years after the storm - Steedman, Scott (Embassy of the State of Qatar, 2015)
"Hurricane Katrina was one of the deadliest, costliest, and most devastating disasters in American history. The Category 5 storm hit the Gulf Coast on August 29, 2005, ravaging large parts of Mississippi, Louisiana, and Alabama. A few hours later the levees protecting New Orleans broke and 80 percent of the city was flooded. At least 1,800 people died and more than a million others left their homes in the largest mass migration in US history. On the other side of the world, His Highness Sheikh Hamad bin Khalifa Al-Thani, the then-Amir of the State of Qatar, watched the tragedy unfold on television. Two weeks later, his government created the Qatar Katrina Fund, pledging $100 million to the recovery of devastated areas. In the months that followed, 18 projects-focusing on housing, health care, and education-received funding. Ten years after the storm, New Orleans and the Gulf Coast are still recovering-but thanks to the efforts of so many, they are thriving. This is the story of Qatar's gift and its role in the renewal of a legendary American city and its surrounding communities". --